Strategi World Food Programme (WFP) dalam Mengatasi Kasus Malnutrisi di Haiti - Pabarri, Enjelina; Tas'an, Ayu Kartika Julianingsih (Journal of International and Local Studies, 2025)
Malnutrition is one of the global issues that has become a major problem in various countries. Haiti is one of the countries with high malnutrition problems. The main hunger triggers in Haiti are conflicts, diseases, and natural disasters, then lead to malnutrition among the Haitian population. The government is trying to address this issue by collaborating with international organizations. The government is working with the WFP in Haiti to address the issue. The WFP directly addresses malnutrition problems in Haiti by implementing programs based on established strategies. This research aims to understand and explain how the World Food Programme (WFP) strategies address malnutrition cases in Haiti. This research uses a descriptive qualitative method, with data obtained through library research by examining various types of data in textbooks, e-books, journals, theses, and articles on the internet, as well as official documents and reports from several official websites of relevant institutions or organizations related to this research topic. The author uses the concept of change written by UNDAF. This concept explains that assistance strategies to those in need can be carried out through four strategies: Focus, Change Analysis, Risk Identification, and Partner and Actor Identification. The results of this study show that WFP has successfully implemented its strategies in Haiti to address malnutrition problems.